The effect of project-based learning integrated STEM toward science process skill of elementary school student - Fitria Wulandari; Putri Permata Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research aims to analyze the effect of the project-based learning ( PjBL ) model on the science process skills of Grade V students at SDN Bringinbendo II. The topic is the water cycle. This study uses a quantitative approach to the experimental method, with the type of research being one group pretest-posttest. The sample in this study was the elementary school SDN Bringinbendo II V-grade students, a total of 21 students. Data collection in this study was by using pretest and posttest question sheets in the form of essay questions with science process skills indicators. Data were analyzed using the paired sample t-test and Eta Squared. The results of the paired sample t-test hypothesis, sig. (2-Tailed) 0.000 <0.05, there is a significant effect (H1 is accepted, and H0 is rejected). The STEM-integrated Project Based Learning ( PjBL ) model affects the science process skills of class V students at SDN Bringinbendo II. In addition, it can be seen how much the increase in the results of the Eta Squared test got 0.508 in the pretest and 0.861 in the post-test. The post-test score has increased, and if t ≥ 0.14 indicates a large influence on the Influence of the STEM (Science, Technology, Engineering, Mathematics) Integrated Project Based Learning Model on the Science Process Skills of Grade 5 Elementary School Students.